2023
DOI: 10.1007/s11164-023-05018-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine-induced synthesis of CdS nanorings for the application in photodegradation

Abstract: In this paper, CdS nanorings synthesized by facile hydrazine-induced microwave method for the photodegradation of pollutants has been reported for the rst time. Different reaction method, microwave power, the category and dosage of pH regulating reagent, reaction temperature and reaction time were investigated. The formation of CdS nanorings from the self-assembly of nanoparticles was attributed to the coordination of hydrazine producing the dipole-dipole interaction among the uniform nanoparticles obtained by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The result indicated that there was no clear adsorption saturation plateau, indicating an irregular pore structure for the three materials. Among these, CdS was assembled into nanochains with internal cavities, and the chains formed stacks with each other, 40 which facilitated the formation of additional pores. When the dosage of CdS was increased by 10 times, the BET surface area of Cu-CPs@ CdS-3 synthesized by the same method was significantly reduced to 20 m 2 •g −1 with a pore size of 18.98 nm (Figure S6).…”
Section: Xrd Structural Analysismentioning
confidence: 99%
“…The result indicated that there was no clear adsorption saturation plateau, indicating an irregular pore structure for the three materials. Among these, CdS was assembled into nanochains with internal cavities, and the chains formed stacks with each other, 40 which facilitated the formation of additional pores. When the dosage of CdS was increased by 10 times, the BET surface area of Cu-CPs@ CdS-3 synthesized by the same method was significantly reduced to 20 m 2 •g −1 with a pore size of 18.98 nm (Figure S6).…”
Section: Xrd Structural Analysismentioning
confidence: 99%
“…In recent years, the variety of heterogeneous photocatalysts has been significantly expanded: there are a number of works aimed at studying the photocatalytic activity of titanium oxide doped with metal and nonmetal atoms [ 15 , 16 ]: for instance, the photocatalytic properties of pure and doped zinc oxide [ 17 , 18 ], nanoscale cadmium sulfide CdS [ 19 ], graphite-like carbon nitride [ 20 ], cerium oxide CeO 2 [ 21 ], CuO [ 22 ], BiOCl, SnO 2 , WO 3 [ 23 ] as well as composite photocatalysts Fe 3 O 4 /TiO 2 [ 24 ], CuBi 2 O 4 /polyaniline [ 25 ], BiFeO 3 -black TiO 2 [ 26 ], layered CuO/ZnO [ 27 ], Dy 2 WO 6 -ZnO [ 28 ] and In 2 O 3 /SnO 2 [ 29 ].…”
Section: Introductionmentioning
confidence: 99%